Sistema Nacional Integrado de Salud: Una aproximación al cuidado de la salud en Uruguay (Repertorio Científico, 2023)
ABSTRACTUruguay is a small country, with a population mostly composed of descendants of European immigrants that, throughout its history, has maintained a high concern for providing medical care to its entire population, regardless of their socioeconomic status. In 2005, after many years of discussion in the academic and political spheres, a reform was initiated in its health system. They wanted to move from a highly fragmented system to a more Bismarck-inspired model. In that sense, the changes were oriented to financing, health care and management. The funding was oriented to a system of payment per capita, adjusted for risk from a National Health Fund. This fund was constituted by contributions from workers, employers and the state. Health care was conceived from an approach focused on the concepts of primary care, of public-private complementation, in order to take advantage of regional economies of scale. In management, the body responsible for public attention was decentralized; thinking about the development of competition between providers focused on recruitment of users. It was understood that, with this view, all providers would offer more quality to attract users. The Ministry of Public Health focused on the functions of controllership, regulation and governance of the system. As for the evolution of these changes: the change in the form of financing and the decentralization of public attention, there were changes quickly implemented by two laws, they were top-down changes. The other changes, although they have made significant progress over the years, are still in process.